Effects of different roadway deicing salts on host-parasite interactions: The importance of salt type. (November 2020) - Buss, Nicholas; Nelson, Kiersten N.; Hua, Jessica; Relyea, Rick A.
Abstract: The application of roadway deicing salts is increasing the salinity of freshwater systems. Increased salinization from salts, such as NaCl, CaCl2 and MgCl2, can have direct, negative impacts on freshwater organisms at concentrations found in nature. Yet, our understanding of how these salts can indirectly impact freshwater organisms by altering important ecological interactions, such as those between hosts and their parasites, is limited. Using a larval amphibian and infectious free-living helminth (i.e. trematode) model, we examined whether exposure to environmentally relevant concentrations of NaCl, CaCl2 and MgCl2 1) influence trematode mortality; 2) alter amphibian-trematode interactions; and 3) alter larval amphibian activity (a behavior associated with parasite avoidance). We found that exposure to CaCl2 greatly reduced trematode survival across all Cl − concentrations (230, 500, 860 and 1000 mg Cl − L −1 ) while NaCl and MgCl2 had no effect. When both host and parasites were exposed to the salts, exposure to NaCl, but not MgCl2 or CaCl2, increased infection. The lack of effect of CaCl2 on infection was likely driven by CaCl2 reducing trematode survival. Exposure to NaCl increased infection at 500 mg Cl − L −1, but not 230 or 860 mg Cl − L −1 . Increased infection was not due to salt exposure altering tadpole behavior. Our results suggest that NaCl can negatively impact amphibian populations indirectly by increasing trematode infections in tadpole hosts. Graphical abstract: Image 1 Highlights: We examined the impacts of roadway deicer exposure on amphibian-trematode dynamics. CaCl2 reduced trematode survival, but MgCl2 and NaCl did not. NaCl increased infection in amphibian hosts, CaCl2 and MgCl2 did not. Lack of effect of CaCl2 on infection likely due to reduced trematode survival. Increased infection by NaCl exposure was not driven by behavioral changes.